Reasons for Growth and Solutions to Combat Money Laundering Through Bitcoin in Iranian Law - Fatemeh Gilak; Davood Khaksar; Mahsa Shiravi (پژوهشهای حقوقی)
The electronic revolution and as a result the increasing growth of electronic commerce and the increasing complexity of financial markets, despite the rich profits it has brought to the government and nations, has also caused the growth of a group of crimes, one of which is money laundering. Money laundering means making the proceeds of criminal activities appear legal and legitimate. In this process, by hiding the illegitimate source of his income, the person spends the resulting money in legitimate and legal ways and causes its original source to disappear, and in the end, his dirty money becomes clean money. On the other hand, today, the desire of individuals and communities to use cryptocurrencies, especially Bitcoin, is increasing, and the use of this currency, despite all its advantages and merits, has provided the basis for the growth of money laundering. In our country, during the last two decades, corruption and money laundering have become two inseparable components of Iran's economy; Therefore, what is very important today is the implementation of an effective and efficient mechanism to combat all types of money laundering, including money laundering through cryptocurrencies. The most important solution currently proposed is to join the FATF convention, recognize and establish strict laws regarding bitcoins due to their digital nature, which can be used to prevent crimes such as money laundering. This research has been done using descriptive-analytical method and using library resources.